Chandler, On The Napoleonic Wars - Mario, Michael (Teaching History: A Journal of Methods, 1996)
Perhaps the greatest ambition of a professional historian is to become so associated with a subject that he or she is instantly recognized as the "leading" authority. Many distinguished scholars are readily known by their work in a certain field-G.R. Elton on the Reformation and C.V. Wedgewood on the English Civil War, to name but two. Similarly, when one thinks of Napoleon, one immediately associates the name David Chandler with him. Chandler is easily identified by his mammoth and weighty tome, The Campaigns of Napoleon, certainly the most exhaustive and lengthy study of the erstwhile French Emperor.